The population of Singapore - Saw, Swee-Hock (Institute of Southeast Asian Studies, 1999)
This comprehensive book deals with population trends and patterns in Sinapore since its founding in 1819. Separate chapters are devoted to population growth and structure, migration, mortality, marriage, divorce, population control, fertility and the labour force. The book concludes by showing that, given the persistent below-replacement fertility rate, the population is expected to peak at about 3.34 million in 2025 and to decline continuously thereafter.